Base Excess or Hyperlactatemia: Identifying the Superior Risk Factor for Increased Morbidity and Mortality in Cardiac Surgery - Ajwad Farogh, Attaullah Younas, Asma Hassan, Naseem Ahmed, Tariq Bashir, Sadaf Iftikhar, Shamila Afshan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Cardiopulmonary bypass in cardiac surgery is often associated with metabolic changes. So, we conducted this study in order to find the supremacy between two risk factors base excess and hyperlactatemia in early prediction of morbidity and mortality in ICU after cardiac surgery. Material and Methods: Intraoperative data of total of 100 patients who had cardiac surgery was recorded. Intraoperative and postoperative data of base excess and lactate levels were recorded at 1st, 6th, 12th and 24th hour in ICU. Two perioperative groups for B.E(Group 1 B.E < +/-2.5 mmol: Group 2 B.E >+/- 2.5 mmol) and lactate (Group 1 Lactate < 3 mmol: Group 2 Lactate>mmol ) were created, Two post-operative groups for B.E(Group 1 B.E < +/-5.0 mmol: Group 2 B.E >+/- 5.0 mmol) and lactate( Group 1 Lactate <5mmol: Group 2 Lactate>5mmol )were created to find their correlation with early postoperative complications. Results: In our study ICU morbidity and mortality was more related to the lactate and base excess values in the early 24 hours. Progressive Hyperlactatemia and constant negative base excess values were both significantly associated with ICU complications. In the CPB period subgroup negative base excess was more superior in predicting ICU prognosis than Lactate. (P-value 0.001) similarly patients divided in subgroup BE >+/- 5mmol/l had demonstrated superiority in making such prediction. Both CPB (0.013) and X.C (0.036) time were associated independently with ICU prognosis. .Longer ventilation times were also associated with bad ICU prognosis. Conclusion: Our study found negative base excess values in the early postoperative period to be superior in predicting ICU morbidity and mortality when studied at subgroup level both peri-operatively and postoperatively.